2003
DOI: 10.1097/01.coc.0000026833.73428.1f
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma: The Impact of Tumor Location and Treatment Strategy on Outcome

Abstract: The purpose of this study was to evaluate how the outcome of patients with extrahepatic cholangiocarcinoma (EHBC) may have been influenced by tumor location and treatment selection. The primary endpoint of this study is overall survival (OS). Between January 1983 and December 1997, 221 patients with biliary tumors were evaluated at Thomas Jefferson University Hospital. Of these, 118 fit the inclusion criteria for this study. The extent of disease was assessed by computed tomography, percutaneous transhepatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 28 publications
0
38
1
Order By: Relevance
“…Similarly, Cheng et al [192] and Schoenthaler et al [193] reported the efficacy of adjuvant radiation for the survival of patients with R1 or R2 resections. Other authors have corroborated the improved survival with adjuvant radiotherapy [194][195][196][197] . Although the bulk of retrospective data suggest that improved survival may be achieved with the use of adjuvant radiation, one prospective study was negative for survival benefit in a selected group of patients with hilar cholangiocarcinoma.…”
Section: Adjuvant Radiotherapymentioning
confidence: 62%
“…Similarly, Cheng et al [192] and Schoenthaler et al [193] reported the efficacy of adjuvant radiation for the survival of patients with R1 or R2 resections. Other authors have corroborated the improved survival with adjuvant radiotherapy [194][195][196][197] . Although the bulk of retrospective data suggest that improved survival may be achieved with the use of adjuvant radiation, one prospective study was negative for survival benefit in a selected group of patients with hilar cholangiocarcinoma.…”
Section: Adjuvant Radiotherapymentioning
confidence: 62%
“…The prognosis is typically poor. Multiple studies have demonstrated the potential efficacy of radiotherapy, with and without chemosensitization, as palliative therapy [1,2] and neoadjuvant therapy prior to conventional resection [3] . Recently, it was reported that liver transplantation with neoadjuvant CRT is more effective than resection for cholangiocarcinoma [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Heron et al 43 compared proximal vs distal tumors and found that adjuvant radiation Ϯ chemotherapy improved median and 2-year survival rates for proximally located tumors compared with observation (median survival 24 vs 13 months, P o 0.01), but showed no significant benefits for distal EHCC. In a contrasting study, 92 patients with either resected EHCC or IHCC were treated adjuvantly with chemotherapy Ϯ radiation (43%) vs observation (54%).…”
Section: Adjuvant Rtmentioning
confidence: 99%